Ajaran Minardi Mursyid dan Korelasinya dengan Aliran Sesat di Indonesia - Rumtianing U.H., Irma (SHAHIH : Journal of Islamicate Multidisciplinary, 2016)
AbstractAlong with the surge of âreligiousâ studies, we apparently have to be selective in attending it, because nowadays many people who attending the Islamic study feel worry aboutÂ what is delivered by the religious teacher, which is considered as âingkar sunnahâ, that is, abandoning the prophetâs hadits, in the explanation of his speech. Similar to what Minardi Mursyid from Surakarta did about his lesson on hadits which has ruined up and spoiled the principles of Islamic aqidah. The investigation of the Fatwa Team of Indonesian Ulema Council (MUI) of Surakarta on Minardi Mursyidâs lesson and the LPPA Tauhid activities found out that Minardi Mursyidâs lesson is similar to the ingkar sunnah sect which has been declared as deviant by MUI and their activities are prohibited by the government.Â Keywords: inkar as-sunnah, deviant sect, Minardi Mursyidâs lessonÂ AbstrakÂ Seiring dengan maraknya gelaran kajian-kajian âagamaâ, kiranya kita tetap harus selektif dalam mengikutinya, karena kini tidak sedikit para jamaah yang hadir dalam sebuah kajian tersebut sudah mulai merasa resah dengan apa yang disampaikan oleh beberapa narasumber yang disinyalir âInkar Sunnah/ menafikan hadits Rasulullah Saw.â dalam paparan kajiannya. Seperti yang dilakukan oleh Minardi Mursyid dari Surakarta mengenai ajaranya tentang hadits yang telah merusak sendi-sendi aqidah Islam dan menodainya. Kajian tim fatwa MUI Surakarta terhadap ajaran Minardi Mursyid dan kegiatan LPPA Tauhid menyimpulkan, bahwa ajaran Minardi Mursyid serupa dengan aliran ingkar sunah yang telah difatwakan sesat oleh MUI dan dilarang kegiatannya oleh pemerintah.Â Kata Kunci: Inkar as-sunnah, aliran sesat, Ajaran Minardi Mursyid